Pre-Columbian metallurgy – Evidence of pyrotechnical ceramics from Rincón Chico, Northwestern Argentina (Andes). (October 2018) - Hein, A.; Gluzman, G.; Kilikoglou, V.
Abstract: An assemblage of 16 fragments of pyrotechnical ceramics used for metallurgical processing was examined by scanning electron microscopy (SEM). The ceramics came from Rincón Chico in the Andes Region of Northwestern Argentina. They were dated as pre-Hispanic. The examined assemblage comprised seven crucible fragments, five mould fragments, two fragments of so-called perforated crucibles and another two fragments which had not been typologically classified yet. Ten fresh fracture samples were prepared, in order to examine the variation of the degree of vitrification in the ceramics. For comparison subsamples were taken from two fragments and subsequently re-fired under controlled conditions at temperatures between 650 °C and 1150 °C. In this way the micromorphology observed in the archaeological samples could be linked to equivalent firing (or operation) temperatures. Apart from the fresh fractures 14 polished sections were prepared in order to examine elemental composition and microstructure. These provided information concerning the selection of raw materials, the potential addition of pumicite as temper and the application of bone ash mixed with fine clay as lining. Furthermore, the spot analysis of metal residues provided information about the processed metal. Highlights: Pre-Columbian pyrotechnical ceramics Pumicite tempering Bone ash lining Perforated crucibles Tin-bronzes